A Simple Program For Estimation of Elements - Muralikrishna, K.V. (Asian Journal of Chemistry, 2010)
The aim of this note is to bring out a simple BASIC program for the quicker estimation of certain elements such as carbon, hydrogen, oxygen, nitrogen, sulphur and phosphorus. This program is considered very necessary for the benefit of the undergraduate students in particular and others in general for undertaking analytical works in the chemistry laboratories.